2022
DOI: 10.1021/acsaem.2c02970
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Strategy for Searching High Lattice Thermal Conductivity Materials

Abstract: Searching for high thermal conductivity materials to efficiently conduct heat for various applications is a long-term endeavor. In 1973, Slack gave four rules for a material with high thermal conductivity, including low atomic mass, strong interatomic bonds, simple crystal structure, and low lattice anharmonicity. Comparing the thermal conductivities of 5 carbon allotropes carefully selected from the Carbon Allotrope Database, we found that a high symmetry operation number SO or a small atom number n in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Actually, studies have shown that symmetry breaking can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which results in an increase in the phonon-phonon scattering phase space to limit lattice heat transport. 26,27 The optimized lattice constants are 3.28 Å and 4.12 Å for b-P and b-Sb, respectively, which are in good agreement with the previous work. 28,29 The calculated band structures are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Actually, studies have shown that symmetry breaking can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which results in an increase in the phonon-phonon scattering phase space to limit lattice heat transport. 26,27 The optimized lattice constants are 3.28 Å and 4.12 Å for b-P and b-Sb, respectively, which are in good agreement with the previous work. 28,29 The calculated band structures are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…2(c), due to the greater number of atoms in the primitive unit cell of GeS 2 , increasing the probability of phonon–phonon scattering. 53 Furthermore, the higher phase space [as observed in Fig. 9(e)] of GeS 2 in the frequency range of 150 cm −1 supports our argument regarding its considerable anisotropic κ l , attributed to both acoustic and low-frequency optical phonons within the 50–150 cm −1 frequency range.…”
Section: Resultssupporting
confidence: 82%
“…63 Compared to conventional carbon structures with high thermal conductivity, carbon materials with ultralow thermal conductivity are desirable in many thermal management applications where heat transfer needs to be minimized to improve the working performance and reliability of electronic devices without overheating and thermal damages. 64 For the convenience of comparison, we summarize the thermal conductivities of Tri-C 20 and some 3D carbon allotropes, including diamond, 59,60 Bcc-C6, 65 graphite, 57,58 lonsdaleite, 66 etc. with respect to their number of atoms and symmetry group numbers in Fig.…”
Section: Thermal Propertiesmentioning
confidence: 99%